Analisis Respon Peserta Didik Terhadap Penggunaan Media Ninja H-BI Pada Pembelajaran IPS - Diani Fifi Susanti; Ida Putri Rarasati; M. Iqbal Baihaqi (Universitas 45 Surabaya, 2023)
Based on observasi it is known that elementary school teachers have not yet developed an active, innovative, and effective learning media. Resulting in learning tends to be monotonous and more dominated by the delivery of material from the teacher. This study discusses the design as well as knowing students' responses to instructional simulations of the NINJA H-BI media design for social studies learning. The method used in this study is the Sugiono model R&D method that was adapted to the six steps of the study. The results showed that the percentage of material experts, media experts, and linguists in a row was 85.8%; 90.7%; and 87.1%. The average expert score is 87.9%, meaning the average expert score has reached the criteria set in the study in the range of 81% -100%, which is very valid, can be used without improvement. While the average percentage of assessment of students' responses by 100%. The conclusion from this study can be stated that the media is suitable for use in social studies learning in elementary schools and get a positive response from students.